Assessment of Knowledge of Nurses Towards Occupational Hazards and Health Safety Measures - Amna, Kaniz; Rehman, Sadia (Biological and Clinical Sciences Research Journal, 2025)
Nurses are regularly exposed to various occupational hazards in healthcare settings, making their awareness and knowledge of health safety measures essential to reduce risk and improve patient care outcomes. Objective: To evaluate the level of knowledge of nurses about occupational hazards and health safety measures in a tertiary care hospital. Methods: A prospective cross-sectional study was conducted at Allama Iqbal Teaching Hospital, D.G. Khan, from February 2024 to February 2025. A total of 100 nurses working across departments including ICU, neurology, medical, urology, pediatrics, obstetrics, nephrology, and orthopedics were included. Data were collected using a structured questionnaire containing 27 items related to general awareness of occupational hazards and specific types of workplace hazards (physical, chemical, mechanical, electrical). The level of knowledge was quantified, and associations with demographic variables such as age and experience were statistically analyzed using SPSS. Results: The overall knowledge score regarding occupational hazards and health safety was 74%. Good knowledge of general concepts was found in 45% of nurses. Full awareness was reported for physical hazards in 42%, chemical hazards in 49%, and mechanical/electrical hazards in 40% of respondents. A statistically significant association was observed between knowledge levels and nurses’ age and work experience (p < 0.05). Conclusion: Nurses demonstrated a satisfactory level of knowledge regarding occupational hazards and health safety. However, efforts should be made to reinforce the practical application of this knowledge through regular training and hospital-based safety protocols to ensure safer working environments.